Parasites of Percophis brasiliensis (Percophidae) benefited from fishery regulations: Indicators of success for marine protected areas? - Braicovich, Paola Elizabeth (2020)
Fishing is the greatest source of anthropogenic impact on global marine resources and the ecosystems supporting them. The decline of many fish stocks has led to the need to apply control and protection measures to promote the recovery of these resources.In the Argentine Sea, a multispecies coastal fishery in the El Rincón region has displayed signs of overexploitation since the beginning of the century. Consequently, temporal and spatial protection measures were implemented in 2004.In previous studies, an independent stock of Percophis brasiliensis in El Rincón was identified based on the parasite communities of fish caught in 2005. However, no subsequent studies using parasite communities have been performed since the protective fishery closure measures were applied.To evaluate parasites as indicators of temporal change in the El Rincón stock of P. brasiliensis after the implementation of these protection measures, a sample from 2018 was compared with that from the previous study, as well as with three other samples. Two of the latter (Argentine Common Fishing Zone and San Matías Gulf) corresponded to previously identified independent stocks in the Argentine biogeographical province and the third was a new sample from the Magellanic Province in southern Patagonian waters.The structure and composition of parasite assemblages of the El Rincón stock of P. brasiliensis differed significantly in 2018, after several years of protective measures. The increased loads observed in several parasite species constitute a promising signal of successful ecosystem recovery. A discrete stock in the Magellanic Province was also identified, providing insights into the population structure of P. brasiliensis along its distributional range, with applications for the sustainable management of this resource.